Modelling the impact of climate change on sediment yield in a highly erodible Mediterranean catchment - Bussi, G; Francés, F; Horel, E; López-Tarazón, J; Batalla, R (Springer Berlin Heidelberg, 2014)
Purpose The assessment of climate change impacts on the sediment cycle is currently a primary concern for environmental policy analysts in Mediterranean areas. Nevertheless, quantitative assessment of climate change impacts is still a complex task. The aim of this study was to implement a sediment model by taking advantage of sediment proxy information provided by reservoir bottom deposits and to use it for climate change assessment in a Mediterranean catchment. Materials and methods The sediment model was utilised in a catchment that drains into a large reservoir. The depositional history of the reservoir was reconstructed and used for sediment sub-model implementation. The model results were compared with gauged suspended sediment data in order to verify model robustness. Then, the model was coupled with future precipitation and temperature scenarios obtained from climate models. Climatological model outputs for two emission scenarios (A2 and B2) were simulated and the results compared with a reference scenario. Results and discussion Model results showed a general decrease in soil moisture and water discharge. Large floods, which are responsible for the majority of sediment mobilisation, also showed a general decrease. Sediment yield showed a clear reduction under the A2 scenario but increased under the B2 scenario. The computed specific sediment yield for the control period was 6.33 Mg ha−1 year−1 , while for the A2 and B2 scenarios, it was 3.62 and 7.04 Mg ha−1 year−1 , respectively. Furthermore, sediment transport showed an increase in its time compression, i.e. a stronger dependence of total sediment yield from the largest event contributions. Conclusions This study shows a methodology for implementing a distributed sediment model by exploiting reservoir sedimentation volumes. This methodology can be applied to a wide range of catchments, given the high availability of reservoir sedimentation data. Moreover, this study showed how such a model can be used in the framework of a climate change study, providing a measure of the impact of climate change on soil erosion and sediment yields.